Predictive value of admission and intrapartum cardiotocography in normal and high risk antenatal women - Nagpal, Anuradha; Tyagi, Mamta; Gupta, Smriti; Manvi Gupta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cardiotocography is the most common method for assessing fetal health and reveals brain oxygenation. This study is done for admission and intrapartum cardiotocography in high- and low-risk pregnancies and its correlation with neonatal outcome. Methods: All high-risk and normal antenatal women with more than 34 weeks of pregnancy and vertex presentation who came to the labor room were included in the study. 200 cases were taken, 100 were in the "high risk group," and the remaining 100 were in the "low risk group." On admission CTG and intrapartum CTG tracing were taken after written and informed consent, neonatal outcomes were observed, and adverse neonatal outcomes were noted. Results: Admission CTG results were unsatisfactory for 9% of women in the high-risk group and none in the low-risk group. Intrapartum NST was non reassuring in 51% of high-risk women and 6% of the low-risk group. Of the total number of neonates admitted to the NICU, 14 were from the low-risk group, while 50 were from the high-risk group. Conclusions: On admission NST in both low and high-risk women, the absence of category III NST predicted the absence of an adverse neonatal outcome most accurately. Even during labor in both high-risk and low-risk women, the absence of category III reassured the fetal well-being most precisely.